2021
DOI: 10.26434/chemrxiv.14377049.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficiency Gains for Thermally Coupled Solar Hydrogen Production in Extreme Cold

Abstract: Hydrogen produced from water using solar energy constitutes a sustainable alternative to fossil fuels, but solar hydrogen is not yet economically competitive. A major question is whether the approach of coupling photovoltaics via the electricity grid to electrolysis is preferential to higher levels of device integration in ‘artificial leaf’ designs. Here, we scrutinise the effects of thermally coupled solar water splitting on device efficiencies and catalyst footprint for sub-freezing ambient temperatures of -… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…regions. 19 Hourly resolved data for location 1 was obtained from NREL's spectral on-demand database [39][40][41] for the year 2019. It inter alia contains the solar spectrum, the ambient temperature, as well as the solar zenith and azimuth angle.…”
Section: Incidence Angle Dependence Of the Eqesmentioning
confidence: 99%
See 4 more Smart Citations
“…regions. 19 Hourly resolved data for location 1 was obtained from NREL's spectral on-demand database [39][40][41] for the year 2019. It inter alia contains the solar spectrum, the ambient temperature, as well as the solar zenith and azimuth angle.…”
Section: Incidence Angle Dependence Of the Eqesmentioning
confidence: 99%
“…Note that the modelling in this work neglects potential device operating failures due to extreme cold temperatures. However, it was shown that the right choice of an electrolyte that sufficiently depresses the freezing point of water enables solar water splitting far below 0 • C. 19 The hourly resolved total spectral irradiance impinging on the device for both locations is shown in Fig. 5d and e.…”
Section: Climatic Input Datamentioning
confidence: 99%
See 3 more Smart Citations